2020 IEEE/RSJ International Conference on Intelligent Robots and Systems (IROS) 2020
DOI: 10.1109/iros45743.2020.9341347
|View full text |Cite
|
Sign up to set email alerts
|

Perception-aware Path Planning for UAVs using Semantic Segmentation

Abstract: In this work, we present a perception-aware pathplanning pipeline for Unmanned Aerial Vehicles (UAVs) for navigation in challenging environments. The objective is to reach a given destination safely and accurately by relying on monocular camera-based state estimators, such as Keyframebased Visual-Inertial Odometry (VIO) systems. Motivated by the recent advances in semantic segmentation using deep learning, our path-planning architecture takes into consideration the semantic classes of parts of the scene that a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
39
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 42 publications
(39 citation statements)
references
References 25 publications
0
39
0
Order By: Relevance
“…In contrast to RRT methods, our set of evaluated viewpoints is unconnected, meaning that we employ a separate path-planner to guide the MAV to the NBV. To this end, we adapt the perception-aware path-planner proposed in [13] to guide the MAV to its goal, while simultaneously directing the sensor at nearby frontiers.…”
Section: Related Workmentioning
confidence: 99%
See 2 more Smart Citations
“…In contrast to RRT methods, our set of evaluated viewpoints is unconnected, meaning that we employ a separate path-planner to guide the MAV to the NBV. To this end, we adapt the perception-aware path-planner proposed in [13] to guide the MAV to its goal, while simultaneously directing the sensor at nearby frontiers.…”
Section: Related Workmentioning
confidence: 99%
“…The perception-aware path-planner presented in [13] uses a two-stage planning process with an initial A * path search based on motion primitives followed by a B-Spline trajectory optimization. Initially, A * searches a collision free path only considering the MAV's position in R 3 .…”
Section: F Perception-aware Path-plannermentioning
confidence: 99%
See 1 more Smart Citation
“…One of the most relevant rival to this work is the perception-aware planner in [8], proposing to generate motion primitives and evaluate them by considering the concentration of landmarks in each area, the probability of collision and the distance to the goal. In [11], however, it is demonstrated that landmark concentration alone is not enough to identify the best areas to fly through, and instead, a perception-aware planner employing semantics to evaluate the quality of the candidate areas for navigation is proposed. Using the semantic segmentation of the SLAM input image as an additional cue in a perception-aware planning algorithm, [11] was shown to achieve the best results in terms of accuracy and robustness of localization to date.…”
Section: Related Workmentioning
confidence: 99%
“…In [11], however, it is demonstrated that landmark concentration alone is not enough to identify the best areas to fly through, and instead, a perception-aware planner employing semantics to evaluate the quality of the candidate areas for navigation is proposed. Using the semantic segmentation of the SLAM input image as an additional cue in a perception-aware planning algorithm, [11] was shown to achieve the best results in terms of accuracy and robustness of localization to date. Nonetheless, it is not able to adapt dynamically to changes in the navigation area at flight time, as it assigns fixed binary informativeness scores to every semantic class in the scene.…”
Section: Related Workmentioning
confidence: 99%